The relationship between the gut microbiome and resistance training: a rapid review - Wagner, A.; Kapounková, K.; Struhár, I. (BMC Sports Science, Medicine and Rehabilitation, 2024)
The human gut microbiome is attracting increasing attention because of its overall effect on health. Several reviews have investigated the impact of physical activity on the gut microbiome; however, these predominantly concentrate on either endurance or a combination of physical activities. This study aims to describe the effect of resistance or strength training on the gut microbiome of a human population. This rapid review follows the guidelines of the Cochrane Rapid Reviews Guidance along with PRISMA. A review of the literature was carried out using articles indexed by PubMed, Scopus, and Web of Science published in the last 12 years. None of the seven studies included find significant change in the gut microbiome in terms of bacterial taxa composition or overall diversity, though the results show that resistance training might decrease the zonulin level and increase mucin production and thereby reduce inflammation in the gut. Interestingly, two studies point to a gut-muscle axis connection and this is discussed in our paper. However, due to the small number of existing studies and certain methodological disagreements, it was hard to find a consensus on the relationship between the gut microbiome and resistance training.